2015
DOI: 10.1089/tmj.2014.0037
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Video-Based Appointments from the Patient's Home: A Patient Survey

Abstract: Background: We examined patient interest in a telehealth model in which the patient supplies the hardware and Internet connectivity to meet with a healthcare provider from his or her home via video call (video appointment). We hoped to understand prospectively the desirability, feasibility, and viability from the patient perspective. Materials and Methods: A phone survey was conducted of a random sample of patients who had been seen in the outpatient setting at a single institution. The sample was stratified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 8 publications
(6 reference statements)
3
45
0
Order By: Relevance
“…The top concern of nonutilizers was lack of patient knowledge about technology. However, 71% of Veterans who engaged in a CVT pain management clinic strongly agreed that they were comfortable with the equipment (Desko & Nazario, ) and a recent survey of patient interest in HBTMH found that comfort in setting up a video call was related to likelihood of accepting or agreeing to a CVT visit (Gardner et al, ). Patients who are not comfortable with technology or have poor confidence in their ability to use CVT may self‐select to continue attending appointments in person.…”
Section: Discussionmentioning
confidence: 99%
“…The top concern of nonutilizers was lack of patient knowledge about technology. However, 71% of Veterans who engaged in a CVT pain management clinic strongly agreed that they were comfortable with the equipment (Desko & Nazario, ) and a recent survey of patient interest in HBTMH found that comfort in setting up a video call was related to likelihood of accepting or agreeing to a CVT visit (Gardner et al, ). Patients who are not comfortable with technology or have poor confidence in their ability to use CVT may self‐select to continue attending appointments in person.…”
Section: Discussionmentioning
confidence: 99%
“…We consider telegenetics holds potential in terms of improving patient access to health professionals and adapting to their wishes or preferences: It allows patients for example to receive genetic care in their own home at a time convenient to them, thereby avoiding traveling time and costs. 4,18 Moreover, telegenetics could allow for increased flexibility and efficiency for counselors too. Previous research has shown that perceptions and evaluations of telegenetics vary between patients and professionals: patients mainly judge telegenetics initiatives as very positive, while professionals are generally positive, but are also aware of communication and technical restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Telehealth in its many forms offers conveniences including increased care accessibility, decreased transportation barriers, and patient empowerment. [4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care.…”
Section: Introductionmentioning
confidence: 99%